Molecular mechanism of a novel root-end filling material containing zirconium oxide on the osteogenic/odontogenic differentiation of human osteosarcoma MG-63 cells - Chen, Yao-Zhong; Huang, Yan; Lü, Xiao-Ying (Frontiers in Bioengineering and Biotechnology, 2023)
Although the novel root-end filling material containing zirconium oxide (NRFM-Zr) which is hydroxyapatite-based may promote osteoblast differentiation, the molecular mechanism remains unclear. The aim of this study is to investigate it underlying the osteogenic/odontogenic differentiation of human osteosarcoma MG-63 cells induced by NRFM-Zr, compared with calcium silicate-based mineral trioxide aggregate (MTA), and glass ionomer cement (GIC). Firstly, three different types of root filling materials were co-cultured with MG-63 cells, and their cell toxicity, alkaline phosphatase (ALP) activity, and calcium ion concentration were evaluated. The results revealed that the NRFM-Zr group showed no significant difference in cell viability compared to the negative control group. After 5 and 7 days of cultivation, both the NRFM-Zr and MTA groups exhibited significantly higher ALP activity compared to the negative control (P<0.05). Moreover, the NRFM-Zr group had the highest calcium ion concentration, while the GIC group was the lowest (P<0.05). Next, gene expression profiling microarray was employed to analyze the impact of the materials on the gene expression profile of MG-63 cells. This analysis identified 2915 (NRFM-Zr), 2254 (MTA) and 392 (GIC) differentially expressed genes, respectively. The results of GO functional analysis and KEGG pathway analysis revealed that differentially expressed genes of NRFM-Zr, MTA and GIC participated in 8, 6 and 0 differentiation-related pathways, respectively. Comparing the molecular mechanisms of osteogenic/odontogenic differentiation induced byi hydroyapatite-based NRFM-Zr and calcium silicate-based MTA, it was found that they share similarities in their molecular mechanisms of promoting osteogenic differentiation. NRFM-Zr primarily promotes differentiation and inhibits cell apoptosis, thereby enhancing osteogenic/odontogenic differentiation of MG-63 cells. Furthermore, the inducing efficacy of NRFM-Zr was found to be superior to MTA.